Influence of polypropylene microfibre (PPMF) dispersion procedure on fresh and hardened rendering mortar properties - Dantas, Sérgio Roberto Andrade (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2020)
This study was carried out to evaluate the influence of a polypropylene microfibre (PPMF) dispersion procedure on fresh and hardened state properties of rendering mortars. Specimens prepared with two different PPMF dispersion procedures were evaluated comparatively with reference specimens prepared without adding PPMF. Changes in the fresh properties were monitored using flow table, squeeze flow, and air-entrainment tests. The hardened state was characterized by capillary water absorption, air-permeability, dynamic elastic modulus (E), tensile strength according to the Brazilian test, and porosity by the Archimedes immersion method. Results show that the fresh mortar properties were not affected by dispersion procedure and all hardened mortar properties were statistically similar, except for the dimensional variation of the specimens. The study also shows that adding polypropylene microfibres in a dispersed form was more effective in terms of controlling total drying shrinkage than directly adding fibres to the cementitious matrix (as recommended by the manufacturer) or the reference mortar.